2001
DOI: 10.1017/s1481803500005315
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis of clavicle fractures: a pilot study

Abstract: Objective: Clavicle fractures are commonly encountered in the emergency department (ED). Our objective was to determine whether emergency physicians can clinically predict the presence and location of a clavicle fracture prior to obtaining x-rays. Methods: Over a 16-month period we prospectively studied ED patients who had injuries compatible with a clavicle fracture. Following clinical examination and prior to obtaining radiographs, ED physicians or senior emergency medicine (EM) residents were asked to predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The question of whether any clavicle imaging is needed at all in cases of high (or low) clinical suspicion has been raised in light of imaging’s associated costs and minimal effect on diagnosis, treatment, and outcomes 25,26 . While our results show clinical suspicion to be reasonably accurate, its PPVs and NPVs were improved in all cases with the addition of US results.…”
Section: Discussionmentioning
confidence: 67%
“…The question of whether any clavicle imaging is needed at all in cases of high (or low) clinical suspicion has been raised in light of imaging’s associated costs and minimal effect on diagnosis, treatment, and outcomes 25,26 . While our results show clinical suspicion to be reasonably accurate, its PPVs and NPVs were improved in all cases with the addition of US results.…”
Section: Discussionmentioning
confidence: 67%
“…Our radiographic follow-up in this study was a mean of five weeks, but we do recognise that only 23% of our patients had fracture union confirmed by radiographs. Some studies have suggested that radiographs are not required at all in the assessment of clavicle fractures [31, 32], but we feel that an initial radiograph to confirm and classify the injury is appropriate even where the fracture is obvious clinically.…”
Section: Discussionmentioning
confidence: 98%
“…Clavicle fractures are frequently seen in the emergency department (ED), accounting for approximately 15% of all paediatric fractures. 1 2 The standard of care is to obtain a radiograph for suspected clavicle fractures prior to treatment. First-line treatment in most children is conservative management with broad arm sling (BAS).…”
Section: Introductionmentioning
confidence: 99%
“… 2–4 Past studies have shown that ED clinicians are able to accurately diagnose clavicle fractures from clinical examination alone. 1–4 Requesting radiographs may be a habit of emergency practice, as it has not been determined if radiographs add valuable information to clinicians’ assessment and influence their management. 1 4–6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation